Effects of Different Silicate Concentrations on Growth Performance of Thalassiosira sp. as Live Feed for Shrimp Larvae - Hendriana, Andri; Wahyudi, Imam Tri; Permatasari, Sheny (Research and Social Study Institute, 2026)
Background: Diatoms require silicate for frustule formation and optimal cell division, making silicate availability a critical factor in improving microalgal production for aquaculture. Thalassiosira sp. is one of the most widely used live feeds in shrimp hatcheries because of its high nutritional value and suitable cell size for larval consumption.Aims: This study evaluated the effects of different silicate concentrations on the growth performance of Thalassiosira sp. by simultaneously assessing cell density, specific growth rate (SGR), and division rate (DR).Methods: A completely randomized design with four treatments was employed: control (without silicate), 15 ppm (SL15), 20 ppm (SL20), and 25 ppm (SL25), each with three replicates. Cell density was monitored daily for 14 days using a haemocytometer, while SGR and DR were calculated from the exponential growth model.Results: The results showed that silicate supplementation significantly affected all growth parameters (p < 0.05). The highest cell density (4.60 × 10⁶ cells mL⁻¹) was obtained in the SL25 treatment on day 12, whereas the highest SGR (29.17 ± 0.32% day⁻¹) and DR (0.422 ± 0.005 divisions day⁻¹) were recorded in SL20. However, Duncan's Multiple Range Test indicated no significant differences between SL20 and SL25 for SGR and DR, suggesting comparable physiological responses at these silicate concentrations. These findings indicate that silicate concentrations between 20 and 25 ppm provide the optimal range for enhancing the growth performance of Thalassiosira sp. and may improve the efficiency of live-feed production for shrimp hatchery applications.Conclusion: Silicate supplementation significantly improve the growth performance of Thalassiosira sp., as reflected by increased cell density, specific growth rate, and division rate.